EFL Students' Perceptions of the Causes of Scientific Writing Anxiety - Norhidayah Fitriani (Institut Agama Islam Negeri Palopo, 2022)
The study was aimed at investigating the levels of scientific writing anxiety and describing the students’ perceptions of the causes of scientific writing anxiety. This research used mixed-method with explanatory sequential as a research design. The students in fifth-semester of English Education IAIN Palangka Raya from 4 classes were involved as the subject of the research. The data was obtained by distributing 51 closed-ended questionnaires and by interviewing 6 participants. The result showed the majority level of writing anxiety is high level with 34 of 51 students or 70.5% students that experienced high level of writing anxiety. In addition, the result also revealed that time constraints, language difficulties, a lack of experience or insufficient writing practice, fear of failure, received negative evaluation from the teacher and classmates were the most significant factors causing students to feel anxious when writing scientific papers.